1987
DOI: 10.1159/000281996
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Evaluation of Prognostic Determinants in Bladder Cancer Patients

Abstract: To clarify the relative importance of factors affecting the survival of patients with bladder cancer, a multivariate analysis by Cox’s proportional hazards model was performed on 264 patients initially treated from 1973 to 1984 at Nagoya University Hospital. Clinicopathological data included in the analysis were sex, age, symptoms, interval from onset of symptoms to first consultation, smoking history and tumor characteristics (location, size, number, shape, histoiogicai grade and stage). The analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 15 publications
(17 reference statements)
1
22
1
Order By: Relevance
“…These results are consistent with several multivariate studies of survival in bladder carcinoma, such as those by Takashi et al 4 and Narayana et al 5 However, in the study by Jahnson et al 6 age did not behave as an independent variable of survival.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with several multivariate studies of survival in bladder carcinoma, such as those by Takashi et al 4 and Narayana et al 5 However, in the study by Jahnson et al 6 age did not behave as an independent variable of survival.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings suggest that the distribution of tumor types may vary by gender and age, and thus the demographics of the selected referral population could affect the distribution of tumor types. Table III compares pathological stage distribution between the present population-based study and representative previously reported studies [8][9][10][11][12][13][14]21,22], all but one of which [14] were based on selected, hospital-or clinic-based patient populations. The hospital-or clinic-based series show a range of non-invasive (stage pTa) tumors between 30 and 49%, compared with 66% in this population-based sample.…”
Section: Discussionmentioning
confidence: 97%
“…Historically, most of the data on the distribution of grade and stage of bladder cancer have been derived from retrospective studies on selected, often hospital-or clinic-based, patient populations [8][9][10][11][12][13]. Such studies are likely to include a disproportionate number of patients with more aggressive or advanced stage tumors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Clark et al [5] studied 1054 patients with locally invasive bladder cancer stratified by age, and found both a worse overall survival and disease-free recurrence in those of advanced age. Others have also found worse overall and CSS with increasing age [6,7]. However, Chahal et al [8] examined the overall 5-year survival for 398 patients with invasive bladder cancer treated with radical RT and RC, and found that age was not an independent predictor of survival for either treatment.…”
Section: Discussionmentioning
confidence: 99%